Development of polymorphic microsatellite markers for Japanese yew, Taxus cuspidata, and T. cuspidata var. nana (Taxaceae)1. (7th July 2016) - Kondo, Toshiaki
Abstract : Premise of the study: Taxus cuspidata (Taxaceae), which is well known for the effective anticancer metabolite paclitaxel (e.g., taxol), is an evergreen needle‐leaved tree widely distributed in eastern Eurasia including Japan. We developed 15 microsatellite markers from this species and confirmed their utility for the dwarf variety nana, which is common in alpine regions along the Sea of Japan. Methods and Results: Thirteen polymorphic loci were characterized for genetic variation in three populations of T. cuspidata . The number of alleles per locus ranged from 11 to 31, with an average of 18.5; the expected heterozygosity ranged from 0.78 to 0.95, with an average of 0.89. All loci were successfully amplified in T. cuspidata var. nana and showed high polymorphism. Conclusions: These markers will be useful for investigating speciation and range formation of T. cuspidata in Japan, and the results will provide crucial information for the conservation of Taxus species.